(untitled) (Fiep Bulletin - online, 2013)
the importance we attribute to the nursing process based on Wanda de Aguiar Horta’s Theory, as a methodology to systematize the assistance on several areas of activity led us to develop this research. OBJECTIVES: to identify the problems which affected two groups of patients subjected to cholecystectomy; to analyze the possible differences, having nursing assistance systematization as a parameter. METHODOLOGY: quasi-experimental study, with quantitative approach, performed in Hospital Universitário Onofre Lopes, in the city of Natal. The population consisted of 60 patients, 30 of which in the experimental group (EG) and 30 in the control group (CG). RESULTS: in the EG, 80 psycho-biological problems were detected in the pre-operative stage, and in the post-operative this number decreased to 72, and from the 369 psycho-social and spiritual problems observed pre-operative, after having been worked upon, none was detected post-operation. As for the CG, the psychobiological pre-operative problems totaled 91 manifestations, growing to 159 in the post-operatiove period, while the psychosocial and spiritual problems totaled 790 manifestations, lowered to 190 in the post-operative. CONCLUSION: the group of www.cofen.br.Consultado shelguedes@hotmail.com glauceamaciel@gmail.com a.elza@uol.com.br 245 c e c e total number of day problems 190 0 159 72 number of detected problems 7 0 19 12 number of problems considered for testing average days per problem 27,14 0 7,95 3,60 standard deviation (days) 29,81 0 10,10 7,68 degrees of freedom P-value 35 0,0263 0,0569 Conclusion Control group average is significantly higher than the experimental group’s Control group average is not significantly higher than the experimental group’s patients assisted with systematization of nursing actions presented a greater number of problems solved more quickly, consequently presenting less problems than the group assisted without systematization, especially in regard to psycho-social and spiritual problems.